Low-temperature and high-airspeed rare-earth-based denitration catalyst as well as preparation method and application thereof
Patent Information
- Application Number
- CN202411503663.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
The existing denitrification catalysts for motor vehicles have low activity and poor water and sulfur resistance under low temperature and high airspeed conditions, making it difficult to meet the practical application needs.
The layer -shaped manganese cobalt composite oxides composed of nano -slices is used as a rare earth dehydrated nitrous catalyst and is prepared by steps such as water heat reactions and vacuum drying. The Mon/CO Murbi of CE/MN/CO is 1: 7: (0.5 ~ 2).
The high -efficiency NOX denitration under low temperature and high -speed conditions has been realized. It has excellent stability and large surface area of water anti -sulfur poisoning, which improves catalytic activity.
Smart Images

Figure CN119368241A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a low-temperature, high-space-velocity rare earth-based denitration catalyst, a preparation method and an application thereof, and belongs to the field of air pollution control technology and environmentally friendly catalytic materials. Background Art
[0002] Nitrogen oxides (NO x ) is PM 2.5 and ozone precursors, seriously endangering the atmospheric environment and human health. x Emissions are gradually being controlled, and NO x Emission reduction has become an important goal of air pollution control. However, 80% of NO x It is emitted during the cold start process, when the flue gas temperature is low and it is difficult to achieve stable and efficient NO x Therefore, the NOx of cold start of motor vehicles is reduced. x Emissions are to control its tail gas NO x The Chinese patents (CN117619430A), (CN108889297B), (CN105944713A) etc. all conduct NO removal in automobile exhaust at low temperature and low air speed. x However, under low temperature (<150℃) and high space velocity conditions, there are problems such as poor denitrification activity and poor water and sulfur resistance, which makes it difficult to meet the actual application requirements. Therefore, the development of new denitrification catalysts with low temperature, high space velocity and good stability has become a hot topic in the field of NOx removal from motor vehicle exhaust. x The key to emission reduction. Summary of the Invention
[0003] The purpose of the present invention is to address the problems of low activity and poor water and sulfur stability of existing denitrification catalysts for motor vehicles under low temperature and high space velocity conditions, and to construct a layered cerium-manganese-cobalt composite oxide with excellent denitrification activity and stability; another object of the present invention is to provide a method for preparing the above-mentioned cerium-manganese-cobalt composite oxide.
[0004] A low-temperature, high-space-velocity rare earth-based denitration catalyst has a microscopic particle morphology of a layered structure composed of nanosheets and a molar ratio of Ce / Mn / Co of 1:7:(0.5-2).
[0005] A method for preparing the above catalyst comprises the following steps:
[0006] (1) Preparation of active component precursor solution
[0007] Adding a metal oxide precursor to deionized water and stirring thoroughly to obtain an active component precursor solution, then adding a pH adjuster and continuing to stir to obtain a uniform precursor solution;
[0008] (2) Preparation of rare earth-based denitrification catalysts
[0009] The precursor solution is transferred to a reactor for hydrothermal reaction, and then the precipitate is collected and centrifuged, washed, vacuum-dried and calcined to obtain a rare earth-based denitration catalyst.
[0010] In the above preparation method, the metal oxide precursors in step (1) are cerium nitrate, manganese nitrate and cobalt nitrate, respectively, and the stirring time is 0.5 to 2 hours.
[0011] In the above preparation method, the pH adjuster in step (1) is urea, the pH value range is 10.5 to 13.5, and the stirring time is 0.5 to 2 hours.
[0012] In the above preparation method, the hydrothermal temperature in step (2) is 120-160° C. and the time is 12-16 hours.
[0013] In the above preparation method, the vacuum drying temperature in step (2) is 80-120° C., and the vacuum drying time is 10-14 h.
[0014] In the above preparation method, the calcination temperature in step (2) is 350-500° C., and the temperature is kept at 2-4 hours in an air atmosphere.
[0015] A rare earth-based denitrification catalyst as described above is particularly suitable for NO in complex flue gas conditions during the cold start phase of a motor vehicle. x Highly efficient purification. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 NH3-SCR denitration curves of different samples of cerium-manganese-cobalt composite oxides of the present invention;
[0017] Figure 2 The graph is a test curve of the long-term water resistance and water-sulfur denitration stability of the cerium-manganese-cobalt composite oxides prepared in Example 3 of the present invention and Comparative Examples 1-2 at 150° C.;
[0018] Figure 3 The sample Ce1Mn7Co1O prepared in Example 3 x SEM image of . DETAILED DESCRIPTION
[0019] The present invention will be further described below with reference to the embodiments, but the protection scope of the present invention is not limited thereto.
[0020] The denitrification performance evaluation method of the catalyst of the present invention is as follows: simulate the flue gas composition, NO xThe inlet concentration is 1000ppm, the inlet concentration of NH3 is 1000ppm, the O2 content is 10%, the H2O content is 5vol.% (added when used), 50ppm SO2 (added when used), and N2 is used as the balance gas. The reaction space velocity (GHSV) is set to 200000h -1 , set the reaction temperature range to 50~350℃, and use flue gas analyzer to monitor NO online before and after the reaction. x concentration changes.
[0021] Example 1
[0022] (1) Preparation of active component precursor solution
[0023] 2.604 g of cerium nitrate (Ce(NO3)3·6H2O), 15.036 g of manganese nitrate solution (Mn(NO3)2, 50 wt%), and 0.873 g of cobalt nitrate (Co(NO3)2·6H2O) were weighed separately, with a Ce / Mn / Co molar ratio of 1:7:0.5, added to deionized water, and stirred for 1 h to obtain a mixed solution A. Then, 3 g of urea was added, the pH value was 12, and stirring was continued for 1 h to obtain a mixed solution B.
[0024] (2) Preparation of rare earth-based denitrification catalysts
[0025] Solution B was transferred to a 100 ml reactor and subjected to a hydrothermal reaction at 140 ° C for 14 hours. The precipitate was then collected by centrifugation (10000 rpm, 3 minutes) and washed with deionized water and anhydrous ethanol. The obtained sample was then vacuum dried at 80 ° C for 12 hours and calcined at 400 ° C for 3 hours to obtain nanosheet cerium manganese cobalt composite oxide. The catalyst with a particle size of 40 to 60 mesh was sieved for denitrification performance testing.
[0026] (3) Denitrification catalytic activity test
[0027] Simulated flue gas composition, NO x The inlet concentration is 1000ppm, the inlet concentration of NH3 is 1000ppm, the O2 content is 10%, the H2O content is 5vol.% (added when used), 50ppm SO2 (added when used), and N2 is used as the balance gas. The reaction space velocity (GHSV) is set to 200000h -1 , set the reaction temperature range to 50~350℃, and use flue gas analyzer to monitor NO online before and after the reaction. x The NH3-SCR denitration rate is >80% within the temperature range of 90-285°C, >90% within the temperature range of 120-270°C, and 100% within the temperature range of 150-215°C.
[0028] Example 2
[0029] (1) Preparation of active component precursor solution
[0030] 2.604 g of cerium nitrate (Ce(NO3)3·6H2O), 15.036 g of manganese nitrate solution (Mn(NO3)2, 50 wt%), and 1.222 g of cobalt nitrate (Co(NO3)2·6H2O) were weighed separately, with a Ce / Mn / Co molar ratio of 1:7:0.7, added to deionized water, and stirred for 1 h to obtain a mixed solution A. 3 g of urea was then added, the pH value was 12, and stirring was continued for 1 h to obtain a mixed solution B.
[0031] (2) Preparation of rare earth-based denitrification catalysts
[0032] Solution B was transferred to a 100 ml reactor and subjected to a hydrothermal reaction at 140 ° C for 14 hours. The precipitate was then collected by centrifugation (10000 rpm, 3 minutes) and washed with deionized water and anhydrous ethanol. The obtained sample was then vacuum dried at 80 ° C for 12 hours and calcined at 400 ° C for 3 hours to obtain nanosheet cerium manganese cobalt composite oxide. The catalyst with a particle size of 40 to 60 mesh was sieved for denitrification performance testing.
[0033] (3) Denitrification catalytic activity test
[0034] Simulated flue gas composition, NO x The inlet concentration is 1000ppm, the inlet concentration of NH3 is 1000ppm, the O2 content is 10%, the H2O content is 5vol.% (added when used), 50ppm SO2 (added when used), and N2 is used as the balance gas. The reaction space velocity (GHSV) is set to 200000h -1 , set the reaction temperature range to 50~350℃, and use flue gas analyzer to monitor NO online before and after the reaction. x The NH3-SCR denitration rate is >80% within the temperature range of 90-285°C, >90% within the temperature range of 105-270°C, and 100% within the temperature range of 150-215°C.
[0035] Example 3
[0036] (1) Preparation of active component precursor solution
[0037] 2.604 g of cerium nitrate (Ce(NO3)3·6H2O), 15.036 g of manganese nitrate solution (Mn(NO3)2, 50 wt%), and 1.746 g of cobalt nitrate (Co(NO3)2·6H2O) were weighed separately, with a Ce / Mn / Co molar ratio of 1:7:1, added to deionized water, and stirred for 1 h to obtain a mixed solution A. 3 g of urea was then added, the pH value was 12, and stirring was continued for 1 h to obtain a mixed solution B.
[0038] (2) Preparation of rare earth-based denitrification catalysts
[0039] Solution B was transferred to a 100 ml reactor and subjected to a hydrothermal reaction at 140 ° C for 14 hours. The precipitate was then collected by centrifugation (10000 rpm, 3 minutes) and washed with deionized water and anhydrous ethanol. The obtained sample was then vacuum dried at 80 ° C for 12 hours and calcined at 400 ° C for 3 hours to obtain nanosheet cerium manganese cobalt composite oxide. The catalyst with a particle size of 40 to 60 mesh was sieved for denitrification performance testing.
[0040] (3) Denitrification catalytic activity test
[0041] Simulated flue gas composition, NO x The inlet concentration is 1000ppm, the inlet concentration of NH3 is 1000ppm, the O2 content is 10%, the H2O content is 5vol.% (added when used), 50ppm SO2 (added when used), and N2 is used as the balance gas. The reaction space velocity (GHSV) is set to 200000h -1 , set the reaction temperature range to 50~350℃, and use flue gas analyzer to monitor NO online before and after the reaction. x The NH3-SCR denitration rate is >80% within the temperature range of 90-285°C, >90% within the temperature range of 105-270°C, and 100% within the temperature range of 150-215°C.
[0042] Figure 2 The catalyst was used to remove NO at 150℃ by introducing 5vol.H2O and 5vol.H2O+50ppm SO2. x Efficiency curve of Ce1Mn7Co1O. It can be seen that after 5vol.H2O is introduced for 1 hour, x The denitrification activity of the catalyst decreased from 100% to 83%, and then stabilized at around 81%. After the water was cut off, the activity was almost completely restored. This shows that the catalyst has excellent resistance to H2O poisoning. At the same time, after the introduction of 5 vol. H2O and 50 ppm SO2 at 150 ° C, Ce1Mn7Co1O x The NO conversion rate of the catalyst gradually decreased, but eventually stabilized at around 80%. After the water and sulfur were cut off, the activity recovered to around 94.8%. Figure 3 The SEM image of the catalyst shows a layered structure composed of multiple flat nanosheets, which gives it a larger specific surface area, exposing more active sites on the surface, which is beneficial to improving catalytic activity. x The catalyst has excellent low-temperature denitrification activity and stability against water-sulfur poisoning.
[0043] Example 4
[0044] (1) Preparation of active component precursor solution
[0045] 2.604 g of cerium nitrate (Ce(NO3)3·6H2O), 15.036 g of manganese nitrate solution (Mn(NO3)2, 50 wt%), and 2.095 g of cobalt nitrate (Co(NO3)2·6H2O) were weighed separately, with a Ce / Mn / Co molar ratio of 1:7:1.2, added to deionized water, and stirred for 1 h to obtain a mixed solution A. 3 g of urea was then added, the pH value was 12, and stirring was continued for 1 h to obtain a mixed solution B.
[0046] (2) Preparation of rare earth-based denitrification catalysts
[0047] Solution B was transferred to a 100 ml reactor and subjected to a hydrothermal reaction at 140 ° C for 14 hours. The precipitate was then collected by centrifugation (10000 rpm, 3 minutes) and washed with deionized water and anhydrous ethanol. The obtained sample was then vacuum dried at 80 ° C for 12 hours and calcined at 400 ° C for 3 hours to obtain nanosheet cerium manganese cobalt composite oxide. The catalyst with a particle size of 40 to 60 mesh was sieved for denitrification performance testing.
[0048] (3) Denitrification catalytic activity test
[0049] Simulated flue gas composition, NO x The inlet concentration is 1000ppm, the inlet concentration of NH3 is 1000ppm, the O2 content is 10%, the H2O content is 5vol.% (added when used), 50ppm SO2 (added when used), and N2 is used as the balance gas. The reaction space velocity (GHSV) is set to 200000h -1 , set the reaction temperature range to 50~350℃, and use flue gas analyzer to monitor NO online before and after the reaction. x The NH3-SCR denitration rate is >80% within the temperature range of 90-285°C, >90% within the temperature range of 105-270°C, and 100% within the temperature range of 150-215°C.
[0050] Example 5
[0051] (1) Preparation of active component precursor solution
[0052] 2.604 g of cerium nitrate (Ce(NO3)3·6H2O), 15.036 g of manganese nitrate solution (Mn(NO3)2, 50 wt%), and 1.746 g of cobalt nitrate (Co(NO3)2·6H2O) were weighed separately, with a Ce / Mn / Co molar ratio of 1:7:1, added to deionized water, and stirred for 1 hour to obtain a mixed solution A. Then, 2 g of urea was added, the pH value was 10.5, and stirring was continued for 1 hour to obtain a mixed solution B.
[0053] (2) Preparation of rare earth-based denitrification catalysts
[0054] Solution B was transferred to a 100 ml reactor and subjected to a hydrothermal reaction at 140 ° C for 14 hours. The precipitate was then collected by centrifugation (10000 rpm, 3 minutes) and washed with deionized water and anhydrous ethanol. The obtained sample was then vacuum dried at 80 ° C for 12 hours and calcined at 400 ° C for 3 hours to obtain nanosheet cerium manganese cobalt composite oxide. The catalyst with a particle size of 40 to 60 mesh was sieved for denitrification performance testing.
[0055] (3) Denitrification catalytic activity test
[0056] Simulated flue gas composition, NO x The inlet concentration is 1000ppm, the inlet concentration of NH3 is 1000ppm, the O2 content is 10%, the H2O content is 5vol.% (added when used), 50ppm SO2 (added when used), and N2 is used as the balance gas. The reaction space velocity (GHSV) is set to 200000h -1 , set the reaction temperature range to 50~350℃, and use flue gas analyzer to monitor NO online before and after the reaction. x The NH3-SCR denitration rate is >80% within the temperature range of 105-270°C, >90% within the temperature range of 120-240°C, and 100% within the temperature range of 180-210°C.
[0057] Example 6
[0058] (1) Preparation of active component precursor solution
[0059] 2.604 g of cerium nitrate (Ce(NO3)3·6H2O), 15.036 g of manganese nitrate solution (Mn(NO3)2, 50 wt%), and 1.746 g of cobalt nitrate (Co(NO3)2·6H2O) were weighed separately, with a Ce / Mn / Co molar ratio of 1:7:1, added to deionized water, and stirred for 1 hour to obtain a mixed solution A. Then 4 g of urea was added, the pH value was 13.5, and stirring was continued for 1 hour to obtain a mixed solution B.
[0060] (2) Preparation of rare earth-based denitrification catalysts
[0061] Solution B was transferred to a 100 ml reactor and subjected to a hydrothermal reaction at 140 ° C for 14 hours. The precipitate was then collected by centrifugation (10000 rpm, 3 minutes) and washed with deionized water and anhydrous ethanol. The obtained sample was then vacuum dried at 80 ° C for 12 hours and calcined at 400 ° C for 3 hours to obtain nanosheet cerium manganese cobalt composite oxide. The catalyst with a particle size of 40 to 60 mesh was sieved for denitrification performance testing.
[0062] (3) Denitrification catalytic activity test
[0063] Simulated flue gas composition, NO x The inlet concentration is 1000ppm, the inlet concentration of NH3 is 1000ppm, the O2 content is 10%, the H2O content is 5vol.% (added when used), 50ppm SO2 (added when used), and N2 is used as the balance gas. The reaction space velocity (GHSV) is set to 200000h -1 , set the reaction temperature range to 50~350℃, and use flue gas analyzer to monitor NO online before and after the reaction. x The NH3-SCR denitration rate is >80% within the temperature range of 102-285°C, >90% within the temperature range of 120-270°C, and 100% within the temperature range of 180-215°C.
[0064] Comparative Example 1
[0065] (1) Preparation of active component precursor solution
[0066] 2.604 g of cerium nitrate (Ce(NO3)3·6H2O) and 15.036 g of manganese nitrate solution (Mn(NO3)2, 50 wt%) were weighed separately, with a Ce / Mn molar ratio of 1:7, added to deionized water, and stirred for 1 h to obtain a mixed solution A. Then, 3 g of urea was added, the pH value was 12, and stirring was continued to obtain a mixed solution B.
[0067] (2) Preparation of rare earth-based denitrification catalysts
[0068] Solution B was transferred to a 100 ml reactor and subjected to a hydrothermal reaction at 140 ° C for 14 hours. The precipitate was then collected by centrifugation (10000 rpm, 3 minutes) and washed with deionized water and anhydrous ethanol. The obtained sample was then vacuum dried at 80 ° C for 12 hours and calcined at 400 ° C for 3 hours to obtain nanosheet cerium manganese cobalt composite oxide. The catalyst with a particle size of 40 to 60 mesh was sieved for denitrification performance testing.
[0069] (3) Denitrification catalytic activity test
[0070] Simulated flue gas composition, NO xThe inlet concentration is 1000ppm, the inlet concentration of NH3 is 1000ppm, the O2 content is 10%, the H2O content is 5vol.% (added when used), 50ppm SO2 (added when used), and N2 is used as the balance gas. The reaction space velocity (GHSV) is set to 200000h -1 , set the reaction temperature range to 50~350℃, and use flue gas analyzer to monitor NO online before and after the reaction. x The NH3-SCR denitration rate is >80% within the temperature range of 105-285°C, >90% within the temperature range of 130-270°C, and 100% within the temperature range of 183-215°C.
[0071] Comparative Example 2
[0072] (1) Preparation of polyol solution
[0073] Weigh 8 ml of glycerol and 56 ml of isopropyl alcohol, place them in a 100 ml beaker, and continue stirring until a transparent and uniform polyol solution is obtained.
[0074] (2) Preparation of active component precursor solution
[0075] 2.604 g of cerium nitrate (Ce(NO3)3·6H2O) and 15.036 g of manganese nitrate solution (Mn(NO3)2, 50 wt%) were weighed separately, with a Ce / Mn molar ratio of 1:7, and added to the above-mentioned stirred solution A, and stirred for 1 h to obtain a mixed solution B.
[0076] (3) Preparation of porous micron-sphere cerium-manganese-cobalt composite oxide
[0077] Solution B was transferred to a 100 ml reactor and subjected to a hydrothermal reaction at 140°C for 14 hours. The precipitate was then collected by centrifugation (10,000 rpm, 3 minutes) and washed with deionized water and anhydrous ethanol. The resulting sample was then vacuum dried at 80°C for 12 hours and calcined at 400°C for 3 hours to obtain porous micron-spherical cerium-manganese composite oxide. The catalyst with a particle size of 40 to 60 mesh was sieved for denitrification performance testing.
[0078] (4) Denitrification catalytic activity test
[0079] Simulated flue gas composition, NO x The inlet concentration is 1000ppm, the inlet concentration of NH3 is 1000ppm, the O2 content is 10%, the H2O content is 5vol.% (added when used), 50ppm SO2 (added when used), and N2 is used as the balance gas. The reaction space velocity (GHSV) is set to 200000h -1 , set the reaction temperature range to 50~350℃, and use flue gas analyzer to monitor NO online before and after the reaction.x The NH3-SCR denitrification rate is >60% within the temperature range of 120-300℃, and >90% within the temperature range of 165-290℃.
Claims
1. A low-temperature, high-space-velocity rare earth-based denitration catalyst, characterized in that The microscopic particle morphology of the catalyst is a layered structure composed of nanosheets, and the molar ratio of Ce / Mn / Co is 1:7:(0.5-2).
2. A method for preparing the catalyst according to claim 1, characterized in that: The method comprises the following steps: (1) Preparation of active component precursor solution Adding a metal oxide precursor to deionized water, stirring thoroughly to obtain an active component precursor solution, then adding a pH adjuster, and continuing to stir to obtain a uniform precursor solution; (2) Preparation of rare earth-based denitrification catalysts The precursor solution is transferred to a reactor for hydrothermal reaction, and then the precipitate is collected and centrifuged, washed, vacuum dried and calcined to obtain a rare earth-based denitrification catalyst.
3. The method according to claim 2, characterized in that The metal oxide precursors in step (1) are cerium nitrate, manganese nitrate and cobalt nitrate, respectively, and the stirring time is 0.5 to 2 hours.
4. The method according to claim 2, characterized in that: The pH adjusting agent in step (1) is urea, the pH value range is 10.5 to 13.5, and the stirring time is 0.5 to 2 hours.
5. The method according to claim 2, characterized in that: The hydrothermal temperature in step (2) is 120-160° C. and the time is 12-16 hours.
6. The method according to claim 2, characterized in that: The vacuum drying temperature in step (2) is 80-120° C., and the vacuum drying time is 10-14 hours.
7. The method according to claim 2, characterized in that: The calcination temperature in step (2) is 350-500° C. and the temperature is kept at 2-4 hours in an air atmosphere.
8. A rare earth-based denitration catalyst as claimed in claim 1 is particularly suitable for the removal of NO in complex flue gas conditions during the cold start phase of a motor vehicle. x Highly efficient purification.
Citation Information
Patent Citations
Flue gas denitration catalyst and preparation method and application thereof
CN102166522A
Denitration catalyst and preparation method thereof
CN107175103A
Preparation method of spherical low-temperature denitration catalyst, spherical low-temperature denitration catalyst prepared by method and application of catalyst
CN109745997A
CO-SCR denitration catalyst as well as preparation method and application thereof
CN111229212A
Vanadium-free rare earth-based wide-temperature denitration catalyst with hollow structure and preparation method thereof
CN115672312A
Cited By
Manganese-cobalt composite oxide loaded CeO2 denitration catalyst and preparation method thereof
CN119771439A
A manganese-cobalt composite oxide supported CeO2 denitration catalyst and its preparation method
CN119771439B